Investment and Profitability of Community Heating Systems Using Bioenergy in Finland: Opportunities and Challenges - Raghu KC (MDPI AG, 2021)
Oil heating systems are abundant in rural Finland and they need to be replaced by renewable energy as Finland aims to be carbon neutral by 2035. Bioenergy, one of the renewable energies, is a common source of energy in Finland as the country is rich in forest resources. In Finland, combined heat and power plants utilize such resource to produce district heat and electricity but Finnish rural areas do not have access to the district heating network. However, there are potential scenarios where community heating could be possible using portable chip-fired heating systems (heat containers). Ultimately, the cost of heating is an important factor for the consumers and the cost of investment is likely to put off any interest from the communities. In this research, we explored the cost and profitability of heat container investments in rural Finland and examined the challenges for the energy transition away from oil heating systems, as well as the opportunities decentralized biomass-fired heating systems might bring. The results of this research indicate that the price of heat produced in heat containers is comparatively higher than district heating, which is commonly used in cities in Finland, but is cost-competitive compared to oil heating depending on the price of oil. For example, the current price of LFO (~1 EUR/l) generates costlier heat than the 300 kW heat container provides. Firing wood pellets in the heat container is not economically viable due to expensive raw material but smaller-sized heat container (110 kW) firing wood chips could provide cost-competitive heat if uptime is raised to >2700 h/year. There are socio-economic impacts and value-added effects on the rural region due to utilization of local resource instead of imported LFO but there remain challenges and barriers such as high initial investment, low investment support and lack of policies focused on decentralised energy enterprises.